2014
DOI: 10.1074/mcp.m113.035873
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Secretome and Extracellular Proteome of the Potato Late Blight Pathogen Phytophthora infestans

Abstract: Oomycetes are filamentous organisms that cause notorious diseases, several of which have a high economic impact. Well known is Phytophthora infestans, the causal agent of potato late blight. Previously, in silico analyses of the genome and transcriptome of P. infestans resulted in the annotation of a large number of genes encoding proteins with an N-terminal signal peptide. This set is collectively referred to as the secretome and comprises proteins involved in, for example, cell wall growth and modification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 74 publications
1
80
1
Order By: Relevance
“…By contrast, histone H3 and cytoplasmic eGFP were detected only in the mycelium, indicating little or no contamination of the CF with intracellular proteins. Protein secretion from cultured P. infestans hyphae without haustoria is well documented (Torto et al ., ; Meijer et al ., ). However, it was not possible here to observe the sites of secretion in vitro using confocal microscopy, as the fusion protein would be rapidly diluted upon secretion.…”
Section: Resultsmentioning
confidence: 97%
“…By contrast, histone H3 and cytoplasmic eGFP were detected only in the mycelium, indicating little or no contamination of the CF with intracellular proteins. Protein secretion from cultured P. infestans hyphae without haustoria is well documented (Torto et al ., ; Meijer et al ., ). However, it was not possible here to observe the sites of secretion in vitro using confocal microscopy, as the fusion protein would be rapidly diluted upon secretion.…”
Section: Resultsmentioning
confidence: 97%
“…The latter encyst on plant contact and germinate, thereby forming an appressorium at the tip, from which a penetration peg emerges that mediates entry into the epidermal cells of the host plant. Cell wall‐degrading enzymes are secreted that may facilitate the penetration process (Brouwer et al ., ; Meijer et al ., ). After penetration, hyphae colonize the mesophyll, where they grow intracellularly and form haustoria inside the host cells (Whisson et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Both BBEs and α-CAs oxidoreductases are likely involved in pathogen detoxification processes and triggering host cell death responses [28]. In a recent study, Meijer and coworkers confirmed the secretion of five berberine-like proteins in P. infestans by using a proteomic approach [62]. Although their function in Phytophthora has not been fully elucidated, it has been hypothesized that they may act as virulence factors or as protecting agents against plant counter defenses [28], [62], [63].…”
Section: Discussionmentioning
confidence: 99%